Litoralonimy i pelagialonimy w strefie Jeziora Szczutowskiego i Urszulewskiego - Gałkowski, Artur; Gliwa, Renata; Agnieszka Gralak (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The paper presents the results of research on microtoponymy expressed by litoralonyms and pelaghialonyms of two neighboring lakes in the Dobrzyńskie Lake District (Eastern extremity of Dobrzyń nad Wisłą Land): Lakes Szczutowskie and Urszulewskie. Litoralonyms (L) are defined as names of inhabited or uninhabited points and area of the waterfront; pelaghialonyms (P) instead are names of lake fishing depths or areas on the surface of the water, recognized and used by local communities. The names of the L- and P-type meet in many cases, features interchangeable or joint in their function. They are motivated by topography, forms of the surrounding landscape and the natural state of the lake, but especially by a large extent of the human factor, i.e. anthroponyms associated with building plots along the shoreline, and the names of the components of rural infrastructure.